Quantitative dynamic evaluation HBsAg in blood in comparison to viral load level in patients with chronic HBV-monoinfection - K. R. Dudina; O. O. Znoyko; S. A. Shutko; Ye. A. Klimova; L. Ye. Kuzina; D. M. Braginsky; N. P. Blokhina; N. D. Yushchuk (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2011)
Aim of investigation. Quantitative analysis of HBsAg contents in the blood in relation to HBV viremia level in patients with various variants of natural course of chronic HBV-infection at dynamic evaluation within 1,5–2 years.Material and methods. Overall 135 patients with chronic HBV-monoinfection were included in original study. Dynamic assessment of HBV viremia level by polymerase chain reaction and quantitative assessment of blood HBsAg by chemiluminescence was carried out.Results. Blood HBsAg concentration significantly differed between НВе-positive and НВе-negative phases of chronic HBV-infection. At analysis of serum HBsAg fluctuations in НВе-negative chronic hepatitis B patients no correlation of HBsAg concentration with the level of HBV viremia was revealed at dynamic observation for 1,5 to 2 years. Received data on low HBsAg concentration in a part of inactive HBV carriers allow to consider, that quantitative assessment of HBsAg contents as a supplemental criterion for diagnosis of «hepatitis B virus inactive carriage».